THE STUDY OF THE APPEARENCE OF ANISOTROPIC PROPERTIES OF POLYMER NANOCOMPOSITES DUE TO PRELIMINARY DEFORMATION UNDER BIAXIAL LOADING - Komar, L.A.; Mokhireva, K.A.; Morozov I.А. (Perm Federal Research Centre Journal, 2017)
Investigation of mechanical properties of anisotropic elastomer composites reinforced with carbon black particles of different brands showed a significant difference in the behavior of samples for both strength characteristics and the degree of softening. The cross-shaped samples were subjected to uniaxial and biaxial tension in two orthogonal directions on the Zwick biaxial testing machine. Anisotropy of the mechanical properties is strongly marked for the samples, which have larger hysteresis loop during the first loading-unloading cycle.